"Sorry for what we did": A Social Psychological Understanding of Political and Intergroup Apologies (Introduction to the Special Issue). Issue 1 (17th February 2022) - Gkinopoulos, Theofilos; Sagherian-Dickey, Thia; Schaafsma, Juliette
Research on political apologies spans sociopolitical contexts and disciplines and methodological frameworks. In the rise of interest in political apologies, especially in light of 'the age of apologies', social psychologists strive to understand mechanisms of issuing, perception and evaluation of political apologies from many perspectives. This special issue aims to highlight the important role of social psychological theory in understanding political apologies and deepening knowledge in this field. The papers, which comprise the special issue, offer a detailed and comprehensive study of political apology, including both theoretical and methodological lens to enrich understanding of the topic. Concluding, all the papers of this special issue can be of interest in academics and researchers, as well as policy-makers and other stakeholders beyond academia.